Design of an Electromyograph Equipped with Digital Neck Angle Elevation Gauge - Ahmad Kamil Solihin; Endro Yulianto; Her Gumiwang Ariswati; K. K. Mujeeb Rahman (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2021)
The development of technology also affects human health, including body posture due to poor human position when using gadgets, both smartphones, and laptops. This study is design a tool that can measure the elevation of a person's neck angle equipped with electromyography, to help health workers, medical rehabilitation doctors to diagnose and provide treatment to patients with a bent head posture or forward head posture. In this research, an electromyography module is designed which consists of a series of instruments, a pre-amplifier circuit, a high pass filter, a low pass filter, and a dc offset regulator to be converted to digital so that it can be displayed on a laptop. In this study, the tapped muscle was the upper trapezius muscle using disposable electrodes. Meanwhile, to measure the angular elevation, the MPU 6050 sensor is used to measure the movement of the head forward. The frequency of the electromyography signal is 20-500 Hz. For software or display readings from this tool is Delphy. Meanwhile, the microcontroller used for ADC communication is Arduino Uno. From the research, it was found that the neck angle elevation gauge has a 0,597% error rate, for conditioning conducted on respondents, all respondents experienced a decrease in amplitude on the same frequency spectrum in the last ten minutes. Meanwhile, a drastic decrease occurred at the neck angle of 60°. Thus, it can be concluded that the forward position of the head affects the frequency spectrum of the neck muscles.